2008
DOI: 10.1158/1535-7163.mct-08-0288
|View full text |Cite
|
Sign up to set email alerts
|

Anti-integrin monoclonal antibody CNTO 95 enhances the therapeutic efficacy of fractionated radiation therapy in vivo

Abstract: Selective targeting of up-regulated integrins on tumor cells is a novel antiangiogenesis strategy for treating solid tumors. CNTO 95 is a fully human anti-A v integrin monoclonal antibody and has shown antitumor activity when used as a single agent in preclinical studies. We previously showed that radiation combined with an integrin A v B 3 antagonist cRGD peptide increased the therapeutic efficacy of radiation in preclinical tumor models. We hypothesized that the combination of radiation and CNTO 95 would syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
20
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 32 publications
2
20
0
Order By: Relevance
“…It is also reported that a combined therapy of CNTO 95, the anti-human integrin αv monoclonal antibody and fractionated radiation is more effective than radiation therapy only [15]. Moreover, integrin β1 plays an essential role in mediating post-radiation cancer cell survival [16].…”
Section: Discussionmentioning
confidence: 99%
“…It is also reported that a combined therapy of CNTO 95, the anti-human integrin αv monoclonal antibody and fractionated radiation is more effective than radiation therapy only [15]. Moreover, integrin β1 plays an essential role in mediating post-radiation cancer cell survival [16].…”
Section: Discussionmentioning
confidence: 99%
“…Intetumumab has been reported to inhibit cell adhesion, migration, invasion, and proliferation of endothelial cells and tumor cells in vitro and tumor metastasis in vivo in nude mice with human breast cancer xenografts by inactivating the focal adhesion kinase (FAK) and the docking protein paxillin (1,4). We have previously shown that intetumumab is a potential radiation sensitizer when used in combination with fractionated radiation therapy in human cancer xenograft models in nude mice (5). Data from two multicenter clinical phase I studies in patients with advanced solid tumors have shown that intetumumab was safe and well tolerated either alone or in combination with docetaxel (6,7).…”
Section: Introductionmentioning
confidence: 99%
“…This finding could have major implications when planning the treatment schedules of patients for whom both radiotherapy and chemotherapy are used. On the other hand, an increased uptake of 111 In-RGD 2 at day 15 after irradiation could also be explained by an enhanced, though delayed, expression of integrin a v b 3 , as suggested by other in vivo experiments (27,30,31). Nonetheless, the early and late effects of radiation on tumor vascularity, perfusion, and integrin a v b 3 expression require further investigation.…”
Section: Discussionmentioning
confidence: 75%
“…The sensitivity of the tracer is highlighted in Table 4, where immunohistochemical analysis of integrin b 3 expression remained unaltered after irradiation. Few studies have investigated the expression of integrin a v b 3 after irradiation of tumors; one study also showed that at 3 d after the last radiation fraction, expression of integrin a v b 3 in tumor xenografts was decreased (27). In vitro studies have also previously shown that integrin expression levels on endothelial cells can change within hours after radiotherapy (28,29).…”
Section: Discussionmentioning
confidence: 99%